2008
DOI: 10.1002/uog.5366
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of intraoperative ultrasonography to assess para‐aortic lymph nodes in women with ovarian and uterine corpus malignancy

Abstract: Objectives 42.9, 96.1, 75.0 and 86.0%, respectively. These values were 60.0, 82.0, 47.7 and 88.2% for palpation, and 91.4, 69.5, 45

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In patients with non‐small cell lung cancer, IU was used to guide the dissection of mediastinal lymph nodes with a higher number of nodal stations yielded, and skip nodal metastasis were found in 24% of patients without N1 nodal involvement. Ryo reported that IU was a highly sensitive technique for diagnosing lymph nodes metastases in patients with ovarian and uterine corpus malignancy. Our pilot study revealed the superiority of IU for evaluating RLN lymph nodes in patients with ESCC; the sensitivity and NPV of IU were 100%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with non‐small cell lung cancer, IU was used to guide the dissection of mediastinal lymph nodes with a higher number of nodal stations yielded, and skip nodal metastasis were found in 24% of patients without N1 nodal involvement. Ryo reported that IU was a highly sensitive technique for diagnosing lymph nodes metastases in patients with ovarian and uterine corpus malignancy. Our pilot study revealed the superiority of IU for evaluating RLN lymph nodes in patients with ESCC; the sensitivity and NPV of IU were 100%.…”
Section: Discussionmentioning
confidence: 99%
“…IU is free from the interference of air‐containing organs such as the bowel, lungs, and trachea, and yields high‐quality images. In addition to detecting small lesions, surgeons have applied this technique to identify locoregional lymph nodes in several malignancies . This pilot study was performed to explore the safety, accuracy, and characteristics of IU for identifying RLN lymph nodes in patients with thoracic esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…IU for para-aortic nodes was performed as described previously [8,9]. A patient was placed in the lithotomy position under general anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, we examined the ability of intraoperative ultrasonography (IU) to detect the enlarged para-aortic lymph node in women with gynecological malignancies [8]. IU had superior negative predictive value and sensitivity for para-aortic node metastases.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Intraoperative ultrasonography had superior negative predictive value and sensitivity for para-aortic node metastases compared with palpation during surgery and preoperative CT. In addition, IU seemed to be a promising diagnostic tool for avoiding unnecessary para-aortic lymphadenectomy in women with gynecological malignancies.…”
mentioning
confidence: 98%